A New Extragradient Method for Strongly Pseudomonotone Variational Inequalities. (1st September 2016) - Khanh, Pham Duy
ABSTRACT: This article proposes a new extragradient solution method for strongly pseudomonotone variational inequalities. A detailed analysis of the iterative sequences' convergence and of the range of applicability of the method is provided. Moreover, an interesting class of strongly pseudomonotone infinite dimensional variational inequality problems is considered.